Theoretical Basis For The Development Of Social Competence In Students. - Surayyo Umirzoqova Xudoyberdiyevna (Global Scientific Publishing, 2024)
In this article, students can be viewed as a systematic manifestation of knowledge, skills, abilities, and personal qualities in the development of social competence. Education as a perfect person with intellectual abilities, pedagogical and psychological impact of bringing up students as professionals
Keywords: bringing; students; systematic